Unveiling the Silent Struggle: Depression and Healthcare Utilization Among the Elderly in Rural South India - Kumaran K; Lovling Aarthy Maria; Vijayakarthikeyan M; Sangeetha S S; Prema Priya G; Srishthi R D (National Journal of Community Medicine, 2025)
Background: Depression is one of the mental health issues that has a significant worldwide impact. Findings: Majority of the cases of depression are either underdiagnosed or misdiagnosed as most of the time the symptoms are masked by cognitive decline due to ageing. The study was conducted to estimate the prevalence of depression among the elderly and to identify the sociodemographic and health-related factors associated with geriatric depression.